How do self-efficacy and learning orientation affect performance of university leaders? - Abdul Wahab, ,; Mahmood, Rosli; Ahmad, Shukri (2015)
This research examines the associations between self-efficacy, learning orientation and performance of university leaders.The research through survey instruments design followed a quantitative approach and the population of the research was the leaders of public sector higher education institutions of Punjab, Pakistan.Data collection was made through questionnaires, and the constructs used were adapted from past studies and already examined for reliability.The suggested structural equation model was evaluated with Partial Least Squares (PLS) methods. Findings showed support for the theoretical model that was measured. The results propose that self efficacy and learning orientation is linked with performance.